Associations between body mass index and health-related physical fitness among Chinese university students: a cross-sectional study - Yan Li; Yan Li; Niujin Shi; Yimin Tao (Frontiers in Sports and Active Living)
Obesity among university students is a growing concern with significant implications for physical and mental health. This study aims to examine the associations between body mass index (BMI) and health-related physical fitness among Chinese university students. Data were collected from 14,735 students (9,117 males and 5,618 females) aged 19–25 years. Physical fitness was assessed using the Chinese College Students' Physical Fitness Test, and BMI was calculated as weight (kg) divided by height (m)2. Statistical analyses included Spearman correlation and quadratic regression to explore the relationships between BMI and various physical fitness parameters. Obese students exhibited higher vital capacity but poorer performance in speed, endurance, flexibility, and strength tests compared to their normal-weight counterparts. Quadratic regression analysis revealed a non-linear relationship between BMI and physical fitness scores, with moderate BMI increases initially improving body function and physical quality scores, but further increases leading to declines. Significant sex differences were observed, with males outperforming females in strength and endurance tests, while females excelled in flexibility. Our findings underscore the importance of maintaining a healthy BMI to optimize physical fitness and overall health. Regular physical fitness assessments are essential for identifying at-risk students and implementing targeted interventions. These insights can inform public health strategies and educational programs aimed at reducing obesity prevalence and enhancing the physical well-being of university students.